Analysis of Psychological Issues in Me Before You - Cuevas, Arlene Brilliante; Figuerres, Geraldine; Jose, Angelique; Laude, Laila Marie; Villegas, Carl Joseph (Journal of Language and Literature, 2024)
This study examined the psychological issues and how they affect the behaviors of the protagonists Will and Louisa in the movie Me Before You and their decision-making processes. The research employed a qualitative descriptive approach and incorporated Sigmund Freud's psychoanalytic theory to analyze the film's narrative. Freud's concepts of the id, ego, and superego provide insights into the underlying motivations driving the characters' actions. The findings revealed that Will's struggles with depression, loss of identity, and desire for autonomy drive his decision for assisted suicide while Louisa faces her own challenges with fear of change and societal pressures. The study concluded that experiencing accidents and depression could lead to risky behavior, while highlighting the importance of companionship and understanding, and emphasizing the role of psychological factors in decision-making. Applying Sigmund Freud's psychoanalytic concepts of id, ego, and superego to the protagonists, Will Traynor and Louisa Clark, offers valuable insights into their psychological struggles, enriching the narrative and enhancing its relatability for readers. Future research should explore the ethical implications of assisted suicide, the impact of social isolation on mental health, and the role of humor in caregiving relationships. This will contribute to a deeper understanding of human behavior in challenging circumstances.